Journey and Significance of Quality Control in Medical Safety for China's Plastic Surgery and Aesthetic Medicine Professions - ZHENG Jiaojie; ZHANG Mingzi; SI Loubin; CHEN Jie; WANG Xiaojun; LONG Xiao; XIONG Wei (Xiehe Yixue Zazhi)
Medical quality and safety are essential safeguards for the harmonious society in China, directly affecting people's sense of security and happiness. Continuously improving medical quality and ensuring medical safety are fundamental and essential to implementing the strategies of the Party Central Committee and the State Council, and promoting the construction of a healthy China. In recent years, with the rapid development of China's economy and the people's increasing emphasis on their own health and safety, China's plastic surgery industry has achieved significant progress and yielded outstanding results. However, along with the rapid growth of the industry, medical quality issues and safety accidents have occurred frequently, attracting widespread attention from all sectors of society. This article briefly outlines the history of quality management and quality control for medical quality and safety in China's plastic surgery specialty. It explores the development of quality management from its origin to medical quality management, as well as the responsibilities and contributions of the National Plastic Surgery Quality Control Center in improving industry standards and ensuring patient safety. It aims to provide support for the standardized management of the plastic surgery industry in the future, so as to promote its healthy and sustainable development.